El Excentrico, 1964-03-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
March 5, 1964 [5 de marzo de 1964]. Ano 14, No 10. Cover has photograph of four fashion models with headline, "Fashion Show & Queen Contest at Hawaiian Gaedens Terrace - Auspices American GI Fourm Ladies Auxiliary."